Ballenas - Morgan, Sally, 1957-; Vipond, Jonathan (Laguna Hills, Calif. : QEB, 2006)
Whales are fascinating giants of the deep. Find out how they live, eat, breed, and swim; where in the world they live; and the dangers they have to face.
Includes index.
Translation of: Whales.
Keywords: Whales -- Juvenile literature; Literature